Frequency of three prothrombotic polymorphisms among Syrian population: factor V G1691A, prothrombin G20210A and methylenetetrahydrofolate reductase C677T - Rami A. Jarjour; Samer Ammar; Rami Majdalawi (Taylor & Francis Group, 2017)
Background: Thrombophilia is a multi-factorial disorder caused by inherited and acquired factors. Among the inherited factors are factor V G1691A, prothrombin G20210A and methylenetetrahydrofolate reductase (MTHFR) C677T single nucleotide polymorphisms (SNPs). Aim: The main aim of this study was to assess the incidence of these three SNPs in the Syrian population. Subjects and methods: A total of 200 unrelated healthy Syrians (100 males and 100 females) were recruited. Results: The prevalence of factor V G1691A, prothrombin G20210A and MTHFR C677T SNPs among Syrians is 11.5%, 2.5% and 84.5%, respectively. Prevalence of factor V G1691A and prothrombin G20210A SNPs among apparently healthy Syrian individuals is very high. Conclusion: To the best of the authors knowledge, the Syrian population harbours the highest prevalence of the MTHFR C677T polymorphism compared to all other populations reported so far.